A miniature microstrip quad‐band filtering power divider based on quad‐mode resonators. Issue 15 (28th October 2022) - Sun, Zhengyu; Zhang, Gang; Yang, Xinyu; Tang, Liming; Gu, Xiaojun; Li, Puhong; Tang, Wanchun; Yang, Jiquan
Abstract: A miniature quad‐band filtering power divider (FPD) based on a quad‐mode stub loaded resonator (SLR) is presented. The quad‐band FPD is formed by a proper coupling topology between the open‐ended microstrip line and two pairs of quad‐mode SLRs. Moreover, to achieve good isolation, two resistors are mounted between the symmetrical SLRs with respect to the open‐ended microstrip line properly. The proposed SLR is analysed by the odd‐ and even‐mode analysis method, and four passbands are accordingly introduced. For demonstration, a quad‐band FPD centred at 1.20, 1.66, 1.89 and 2.16 GHz is designed, simulated, fabricated and measured. The measured results have good agreement with simulated ones, which validates the proposed design concept.